Malaria in camps for internally-displaced persons in Uganda: evaluation of an insecticide-treated bednet distribution programme - Spencer, Sebastian; Grant, Alison D.; Piola, Patrice; Tukpoa, Kodzo; Okia, Michael; Garcia, Marlon; Salignon, Pierre; Genevier, Christine; Kiguli, James; Guthmann, Jean-Paul (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2004)
Malaria is a key health problem among displaced populations in malariaendemic areas. Mass distribution of insecticide-treated bednets (ITN) to prevent malaria is often carried out in complex emergencies, but there are few data on the outcome or operational effectiveness of such programmes. In June 2001, Médecins Sans Frontières completed a mass distribution of ITNs (Permanet®) to internally displaced persons in Bundibugyo, southwest Uganda, distributing one to four nets per household, and aiming to provide coverage for all residents. In July 2002, we did a cross-sectional survey using three-stage cluster sampling to evaluate the programme. A total of 1245 individuals from 835 households were interviewed. An ITN was present in 75.6% (95% CI 72.7—78.5) of the households, but only 56.5% (95% CI 52.3—60.4) of individuals were sleeping under an ITN, and nets were often damaged. The prevalence of malarial parasitaemia was 11.2% (95% CI 9.4—13.0), and was significantly lower in ITN users compared to non-users (9.2% vs. 13.8%, relative risk [RR] 0.63, 95% CI 0.46—0.87); ITNs with severe damage remained effective (RR for severely damaged net 0.58, 95% CI 0.35—0.98). There was no significant difference in haemoglobin concentration between ITN users and non-users.
Keywords: Malaria; Insecticide-treated bednets; Programme evaluation; Bednet coverage